PHYSICAL ACTIVITY OF PRIMARY SCHOOL STUDENTS IN THE AREA OF HERZEGOVINA-NERETVA CANTON - Amel Jazvin; Ekrem Čolakhodžić; Adi Palić (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to determine the physical activity of primary school students in the area of Herzegovina-Neretva Canton. The research was conducted on a sample of N=2589 elementary school students from I to IX grades. The obtained data show that out of the total number of respondents, there are more students who do not play sports (54.4%) than students who play sports (45.6%). Only among fourth grade there are more students who play sports (57.8%) than students who don’t play sports (42.2%). In all other classes, there are more students who don’t play sports.